Comparison of percutaneous nephrolithotomy and retrograde intrarenal surgery in treating 20-40 mm renal stones - Atis, Gokhan; Culpan, Meftun; Pelit, Eyup Sabri; Canakci, Cengiz; Ulus, Ismail; Gunaydin, Bilal; Yildirim, Asif; Caskurlu, Turhan (Urology Journal, 2017)
Purpose: To compare the outcomes of percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS) in treating renal stones between 20 and 40 mm in diameter. Materials and Methods: 146 patients, who were treated with RIRS and 146 patients, who were treated with PCNL for renal stones between 20 and 40 mm in diameter were compared retrospectively using a matched-pair analysis. The operative and post-operative outcomes of both groups were analyzed retrospectively. Results: The mean age, gender, body mass index and stone laterality were similar between the groups. The mean stone size was 28.39 ± 4.67 mm for the PCNL group and 25.08 ± 6.07 mm for the RIRS group (P =.21). The mean operative times were statistically longer in the RIRS group, whereas the fluoroscopy times, hospitalization times and post-operative visual analogue scores were statistically higher in the PCNL group. The stone- free rates (SFR) after a single procedure were 91.7% in the PCNL group and 74% in the RIRS group (P = .04). After auxiliary procedures, the overall SFRs reached 94.4% for the PCNL group and 92.3% for the RIRS group (P = .52). No major complications were observed for both groups. Minor complication (Clavien 1-3) rates were 6.8% and 3.4% for the PCNL and RIRS group, respectively (P =.18). Conclusion: RIRS has some advantages over PCNL such as shorter hospitalization times, shorter fluoroscopy times and less post-operative pain in treating renal stones between 20 and 40 mm in diameter. However, PCNL has a higher SFR with only a single session.